A unique destiny : the memoir of the last tsar of Bulgaria, prime minister of a republic /: the memoir of the last tsar of Bulgaria, prime minister of a republic. (2021) - Saxe-Coburg-Gotha, Simeon, 1937-; Courtois, Sébastien de
No abstract available